Optimalisasi Pembelian Perangkat Jaringan Telekomunikasi - Vinny Alifah; Adenan Suhalis (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
Buana Selaras Globalindo company is a company which focuses on providing telecommunication equipment network. The main problem in this research is to find out how the optimal purchase of telecommunication network equipment at Buana Selaras Globalindo Jakarta company. The purpose of this research is to know the number of optimal purchases, the amount of safety provided, the time when repurchase is carried out, the maximum procurement (maximum inventory) and the total cost telecommunication equipment. The data was taken from field and library. The data was analysed with Economic Order Quantity (EOQ). The result of the analysis and discussion shows that the optimal purchase of OTB equipment is 1.429 units, ODP is 1.676 units, Closure is 1.728 units with four times frequency purchase. The safety stock for OTB equipment is 564 units, ODP is 406 units, Closure is 485 units. The ROP for OTB equipment is 1.402 units, ODP is 1.576 units, Closure is 1.729 units. The maximum inventory for OTB equipment is 1.983 units, ODP is 2,082 units, Closure is 2.213 units. The total inventory cost according to the EOQ method for OTB equipment is USD 1.121.144, ODP is USD 1.901.009, Closure is USD 1.976.334